Blood fire vapor smoke - Ray, Shann (Unsolicited Press, 2019)
"A cycle akin to the seasons of life, Blood Fire Vapor Smoke asks questions of the ancient struggle between life and death amidst landscapes new and old. Does ultimate forgiveness answer to ultimate violence in the world? What is the nature of grace? Who determines the fates that move us? A collection of stories opening upon the inner world with the abandon and gravity involved in personal and collective responsibility, the book responds to the present age of engagement, and the collapsing binary of two hungers: violence and forgiveness. Blood Fire Vapor Smoke considers the human myth of regeneration through violence, and the aftermath of loneliness, love, and yearning found in a more merciful expression of human existence. Violence is caught by love, changed, transcended, and transformed into a yearning for restoration, atonement, and the fusion embodied in greater humanity."-- book flap